CIVIL AGREEMENT IN CRIMINAL LAW (Law and world, 2015)
Paragraph 67(1) of the Georgian Criminal Law Code – Civil Agreement is a new institution of the Legislation of Criminal Law, which is giving the opportunity to conditional condemned to be cancelled the conditional sentence before the expiration of the half term and to be released from conviction. The above mentioned institution is a stimulating nor from the point of view of re-socialization of criminal, but it should be mentioned, that simultaneously it is weakening the authorization of judges and is inculcating the hegemony of public prosecutor in material criminal Law. The peculiarity of civil agreement is, that with together with cancelling the conditional sentence authorization for releasing the conviction is delegated to standing. Commission of the issues for cancelling the conditional sentence of the National Agency of Execution of Non-Prison Punishment and Probation. Delegation of authorization for releasing the conviction to the above mentioned commission is contradicting Paragraph 79 of criminal Law, according to which, releasing the conviction is a competence of the court. The ground of civil agreement is rising some questions as well – a Public Prosecutor is able, contemplating the behavior of conditional condemned conclude the civil agreement with him (her) if he (she) is having the will and opportunity to share the own knowledge and experience to the others in certain field. How real is it for the employer to have a will for making the business relationship with condemned? The require of “opportunity” will turn into the temptation of committing any kind of falseness.